2022
DOI: 10.1002/rcs.2483
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous path planning for robot‐assisted pelvic fracture closed reduction with collision avoidance

Abstract: Background: Robot-assisted pelvic fracture closed reduction (RPFCR) positively contributes to patient treatment. However, the current path planning suffers from incomplete obstacle avoidance and long paths. Method:A collision detection method is proposed for applications in the pelvic environment to improve the safety of RPFCR surgery. Meanwhile, a defined orientation planning strategy (OPS) and linear sampling search (LSS) are coupled into the A* algorithm to optimise the reduction path. Subsequently, pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In our study, the robot-assisted group evinced a substantial 20% reduction in surgical time compared to the control group, alongside a remarkable 40% decrease in fluoroscopy frequency, resulting in reduced iatrogenic injury to the patients during the procedure. Moreover, the robot-assisted group in this study demonstrated superior postoperative pain management relative to the control group, which potentially be attributed to the diminished intraoperative puncture-induced damage to the pelvis and surrounding soft tissues ( 13 ). Nonetheless, it is worth considering the marginal 0.4 difference in visual analog scale (VAS) pain scores between the two groups, prompting further exploration into the significance of this subjective perception.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the robot-assisted group evinced a substantial 20% reduction in surgical time compared to the control group, alongside a remarkable 40% decrease in fluoroscopy frequency, resulting in reduced iatrogenic injury to the patients during the procedure. Moreover, the robot-assisted group in this study demonstrated superior postoperative pain management relative to the control group, which potentially be attributed to the diminished intraoperative puncture-induced damage to the pelvis and surrounding soft tissues ( 13 ). Nonetheless, it is worth considering the marginal 0.4 difference in visual analog scale (VAS) pain scores between the two groups, prompting further exploration into the significance of this subjective perception.…”
Section: Discussionmentioning
confidence: 84%
“…The methods described above apply only to lower-extremity fractures. Pan et al (2023) proposed an augmented A* algorithm, 3D-OPS A*, to automatically plan reduction paths for more complex pelvic fractures. However, this approach does not guarantee a minimal resistance force during the reduction.…”
Section: Reduction Path Planningmentioning
confidence: 99%
“…To ensure a smooth reduction procedure, performing any necessary pre-distraction measures, using the minimum force necessary to move the fragments, and selecting the shortest reduction path to minimize any unnecessary movement is important. However, this process is subjective, and surgeons may increase the distance between bones to avoid collisions, which creates iatrogenic injury and leads to secondary soft tissue injury (Pan et al, 2023). During operative procedures, surgeons using RAFR systems may not be able to feel the forces applied to patients in real time, unlike in other treatments.…”
Section: Current Difficulties In Rafr System Researchmentioning
confidence: 99%